Jejak Ketangguhan Inklusif: Pembelajaran dari Desa di Timor, Nusa Tenggara Timur (Kisah Perubahan Program PAR IV CORRECT CIS Timor & CRS) - Selvister Lende Ndaparoka; Alain Oematan (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2026)
This article analyzes the learnings from the PAR IV CORRECT Program implemented by CIS Timor and CRS in Kupang Regency, East Nusa Tenggara. Using an analytical descriptive qualitative approach with a total sampling technique, this study comprehensively examines eight Most Significant Change (MSC) stories from beneficiaries at the village level to understand the dynamics of local resilience development. The thematic analysis shows five main pillars of learning: (1) transformation of mentality from passive to confident agent of change, (2) increasing the strategic role and voice of women in disaster management structures, (3) transition from knowledge to real local-based mitigation actions, (4) strengthening economic independence through the integration of savings and internal lending communities/SILC), and (5) social inclusion that embraces vulnerable groups such as the elderly and low-educated citizens. The study concludes that sustainable disaster resilience does not depend solely on physical infrastructure, but is firmly rooted in inclusive community empowerment, accountability of local agency representation, and integration between disaster preparedness and microeconomic resilience.